“Actualización de la bibliografía de la masonería femenina” - Cuartero Escobés, Susana (2013)
These pages are intended to contribute to studies on gender history developed in recent years, placing themexclusively in the field of Freemasonry. After some brief general considerations about the presence of women inFreemasonry, we focus on the real core of the work: the upgrade and expansion of bibliographical list publishedin 2004 and collected in the Bibliography of Spain and Latin America’s Freemasonry.